Locating Milton : places and perspectives - Festa, Thomas; Ainsworth, David, 1973- (Clemson University Press, 2021)
"The essays in Locating Milton examine Milton's works as the product of the intellectual and experiential influences Milton encountered, while also tracing the ways in which those works themselves express their influence. The volume explores how Milton locates himself within intellectual traditions, and how others locate him"--